Raman spectra of Ag- and Cu- photodoped chalcogenide films - Stronski, A.V.; Vlcek, M.; Stetsun, A.I.; Sklenar, A.; Shepeliavyi, P.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Raman spectra of the chalcogenide vitreous layers (As₄₀S₆₀, As₄₀S₄₀Se₂₀, As₄₀Se₆₀ ) non-doped and photodoped by Ag, Cu were measured. The spectra were analyzed in terms of a molecular model. It was ascertained, that for the spectra of photodoped As₄₀S₆₀, As₄₀S₄₀Se₂₀ layers, the shift of the main bands to the high frequency side and the appearance of the additional scattering bands in the low frequency spectral range are characteristic features. For the spectra of photodoped As₄₀S₆₀ layers, such shift and significant increase in scattering were not observed. Variations in the Raman spectra with photodoping by Ag or Cu are consistent with the supposition concerning normal covalent and coordinative bond formation between metal additives and chalcogen atoms.